Synthesis and biological evaluation of di- and tri-substituted imidazoles as safer anti-inflammatory-antifungal agents - Asif Husain; Sushma Drabu; Nitin Kumar; M M Alam; Sandhya Bawa (Wolters Kluwer Medknow Publications, 2013)
Purpose: In view of the potential pharmacophoric nature of imidazole nucleus, two series of imidazole derivatives, 2,4-disubstituted-1 H-imidazoles (2a-m) and 1,2,4-trisubstituted-1 H-imidazoles (3a-m), were synthesized with an aim of obtaining dual acting compounds i.e., anti-inflammatory and antifungal agents. Materials and Methods: The title compounds were synthesized from 4-methoxyphenyl glyoxal (1) following multistep synthesis, and their structures were established on the basis of modern analytical techniques (IR, NMR and MS). The synthesized imidazoles were tested for their in vivo anti-inflammatory activity. In addition to that, some compounds were also evaluated for their analgesic and ulcerogenic effects. The compounds were also evaluated for their in vitro antifungal activity. Results: Di- and tri-substituted imidazole derivatives (2a-m and 3a-m) were successfully synthesized. In in vivo anti-inflammatory test, six compounds (2 h, 2 l, 3 g, 3 h, 3 l and 3 m) exhibited good anti-inflammatory activity (49.58 to 58.02% inhibition) with minimal GI irritation (severity index; 0.17 to 0.34). These compounds were also tested for their analgesic activity and showed appreciable protection (40.53 to 49.60% protection) against saline-induced writhing test. Indomethacin was used as standard drug for comparison. In antifungal test, two compounds (3 h and 3 l) displayed appreciable antifungal activity (MIC; 12.5 μg mL -1 ) against the fungal strains tested. Conclusion: Two compounds, 2-(4-nitrophenyl)-4-(4-methoxyphenyl)-1-phenyl-1H-imidazole (3 h) and 2,4-di-(4-methoxyphenyl)-1-phenyl-1H-imidazole (3 l), emerged as lead compounds having dual biological activities; good anti-inflammatory as well as antifungal effect with lesser GI irritation.